Dear girl - Rosenthal, Amy Krouse; Rosenthal, Paris; Hatam, Holly (New York : Harper, 2017)
A celebration of girls everywhere that teaches girls to be themselves, be generous and kind, and to dance like no one's watching. Told from the point of view of a girl's guardian, this book delves into the life lessons we all hope to teach the strong girls in our lives.
School Library Journal starred, November 2017
Publisher's Weekly, October 2017
Booklist, September 2017
New York Times, January 2018
Kirkus Review, October 2017
1.3
Keywords: Girls -- Fiction; Conduct of life -- Fiction